How tuition fees affected student enrollment at higher education institutions: The aftermath of a German quasi-experiment - Ralf Minor (Journal for Labour Market Research, 2023)
This study examines the impact of the charging of tuition fees between 2006 and 2014 in several German federal states on the number of first-year student enrollments. Since Germany is known for a tuition-free education policy at public institutions, the fundamental question arises of whether, and if so, to what extent, the temporary tuitions influenced the number of first-year-student enrollments. In this regard, Becker's human capital theory suggests that rising fees should be associated with declining enrollment rates. The analyses to test the hypothesis are based on a longitudinal administrative panel data set for 206 universities and universities of applied sciences from 2003 to 2018; this means there are 3296 observations before, during, and after the tuition treatment. While no previous study has covered the full period of the policy or undertook more aggregate-level analyses, this study applies an analytical research design that uses several panel-data models and robustness checks to examine causal relations based on a quasi-experimental setting. The results of Fixed effects regressions confirm the hypothesized negative impact and even reveal a persistent negative effect of the treatment. The comparison of higher education institutions with and without tuition fees shows that the former institutions lost approximately between 3.8 and 7 percent of their first-year student enrollments on average.
Keywords: I23; I20; I22; I28; H52; H75; 330; Tuition fees; Policy evaluation; Quasi-experiment; Enrollment; Panel data analysis